2020
DOI: 10.1016/j.tranon.2020.100846
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric sarcomas display a variable EpCAM expression in a histology-dependent manner

Abstract: EpCAM is a transmembrane glycoprotein typically overexpressed in cancer of epithelial origin and mainly involved in the epithelial-to–mesenchymal transition (EMT) of tumor cells that spread and disseminate. Strategies for the targeting and capture of EpCAM-expressing tumor cells are showing promise in cancers prone to metastatize, both as diagnostic tools and potential therapies. Sarcomas are among the most aggressive tumors in children, with a common mesenchymal origin that comprises both soft tissue sarcomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…It has been proven that EpCAM expression can be acquired during tumor progression [ 150 ] and is highly expressed in cancer stem cells [ 151 ]. The numbers of CTC-positive in patients with sarcoma and total CTCs in pediatric sarcomas are similar to data previously reported at diagnosis in carcinomas [ 152 ], with progressive disease and poor outcome in patients with the highest EpCAM levels [ 141 ].…”
Section: Ctc Heterogeneity: Epithelial–mesenchymal Transitioned and Stem Cell-like Ctcssupporting
confidence: 86%
See 3 more Smart Citations
“…It has been proven that EpCAM expression can be acquired during tumor progression [ 150 ] and is highly expressed in cancer stem cells [ 151 ]. The numbers of CTC-positive in patients with sarcoma and total CTCs in pediatric sarcomas are similar to data previously reported at diagnosis in carcinomas [ 152 ], with progressive disease and poor outcome in patients with the highest EpCAM levels [ 141 ].…”
Section: Ctc Heterogeneity: Epithelial–mesenchymal Transitioned and Stem Cell-like Ctcssupporting
confidence: 86%
“…Comparative expression of epithelial markers and adhesion molecules indicated heterogeneous expression across types [ 136 , 137 , 138 , 139 ]. Accordingly, a strong variance in EpCAM expression has been documented between histotypes in pediatric sarcomas and the association with patient outcome [ 140 , 141 ]. The metastable EMT state is common in aggressive sarcomas and frequently contributes to drug resistance [ 142 ].…”
Section: Ctc Heterogeneity: Epithelial–mesenchymal Transitioned and Stem Cell-like Ctcsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with renal cell carcinoma (RCC) we demonstrated that the enumeration of CTCs is actionable during targeted therapy and correlates with patients' clinical conditions and final outcome (negative at complete remission, whilst positive over the follow-up period in patients experienced relapse) ( 25 ). In children with soft tissue and bone sarcomas, such as rhabdomyosarcoma, Ewing sarcoma and osteosarcoma, the higher was the expression of EpCAM and the number of CTCs at diagnosis the worse was the prognosis ( 26 ).…”
Section: Discussionmentioning
confidence: 99%